Relationship of social support, mental strength and goal orientation among UiTM football players / Che Nadia Che Samsudin - Che Samsudin, Che Nadia (2012)
The general purpose of this present study is to determine the relationships between social support, mental strength and goal orientation among UiTM football players. These key components (social support, mental strength, and goal orientation) as an integrated whole is most fundamental in ensuring the success especially in any football matches. Therefore this present research attempts to analyze the relationship of these three key fundamental factors as an integrated whole in the local setting. There were a total of 183 respondents who completed the questionnaires which consists of the social support dimension which is social support from parents, coach, friends, and government. Mental strength dimension consists of self confidence, motivational control, and focus control. Goal orientation dimension consists of task and ego orientation. The data analyses were conducted using structural equation modeling (SEM) via AMOS (Analysis of Moment Structures) software package Version 20.0. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were performed to validate the scales. Three measurement models and an overall measurement model were generated and tested in compliance with a stringent purification process for the models. The results of the structural modeling revealed that out of 15 hypotheses tested 12 were supported whereas the remaining 3 were rejected. The results provide evidence that social support from parents, coach, friends and the government directly contribute towards overall social support which in turn, has significant relationships self-confidence, task orientation and ego orientation.